2022
DOI: 10.1177/2156759x221086751
|View full text |Cite
|
Sign up to set email alerts
|

School Counselors and Multicultural Counseling Competencies: Are We as Competent as We Think We Are?

Abstract: We investigated the relationship between self-reported multicultural competence and social issues awareness among school counselors and raters’ assessment of multicultural orientation skills (cultural humility and cultural comfort) using a recorded mock counseling session. Results revealed a positive correlation between multicultural competence and cultural comfort. However, findings demonstrated overestimated self-reports of multicultural competence compared to raters’ assessment of cultural humility. We disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…According to Kendi (2019), school counselors should embrace their roles as social justice advocates and change agents who dismantle systems of oppression by supporting antiracist policies using their actions and expressions of antiracist ideas. Thus, school counselors' potential inability to create safe and equitable spaces for culturally diverse students to engage in their whole selves and consider the impact of their cultural experiences may result in decreased counseling effectiveness (Placeres et al, 2022). The ASCA ethical standards (ASCA, 2022) call for school counselors to be systemic change agents who embrace their roles as advocates, leaders, and collaborators by providing "equitable educational access and success" (p. 1).…”
Section: Antiracist Advocacymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kendi (2019), school counselors should embrace their roles as social justice advocates and change agents who dismantle systems of oppression by supporting antiracist policies using their actions and expressions of antiracist ideas. Thus, school counselors' potential inability to create safe and equitable spaces for culturally diverse students to engage in their whole selves and consider the impact of their cultural experiences may result in decreased counseling effectiveness (Placeres et al, 2022). The ASCA ethical standards (ASCA, 2022) call for school counselors to be systemic change agents who embrace their roles as advocates, leaders, and collaborators by providing "equitable educational access and success" (p. 1).…”
Section: Antiracist Advocacymentioning
confidence: 99%
“…Notably, cultural humility has received most of the attention in the counseling literature (Davis et al, 2018). Those investigating multicultural competence and cultural humility with school counselors have found that these professionals overestimated their multicultural competence compared to their perceived cultural humility by an external reviewer (Placeres et al, 2022). Despite these investigations into culture and advocacy, no studies to date have explored how school counselors advocate against racism.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of consensus contributes to the lack of infusion antiracism within the ASCA (2019a) Professional Competencies and Standards and the draft Council for Accreditation of Counseling and Related Educational Programs (CACREP) (2024) standards. Similarly, the Multicultural Social Justice Counseling Competencies (MSJCC) encompasses counselors’ self‐awareness, cultural knowledge of self/clients, usage of culturally appropriate techniques and interventions, and prioritization of social justice advocacy (Ratts et al., 2016) with little evidence that the model support's positive student outcomes, specifically for students with marginalized identities (Placeres et al., 2022). Instead, multicultural competence frameworks “allow students, most of whom are White, to feel comfortable talking about culture and diversity without discussing uncomfortable topics” (Williams et al., 2021, p. 260), outcomes that are misaligned with the desired intent of antiracism, abolition, and Black futurity (Davis et al, 2022; Tuck & Yang, 2018).…”
Section: Lack Of Consensusmentioning
confidence: 99%
“…For example, in the special issue of Teaching and Supervision in Counseling (Harris et al, 2021) on antiracist counselor education, 7 out of the 10 articles were conceptual, and only 4 included definitions of antiracism ranging from acknowledging racism as a root cause of oppression (Bertrand, 2021;Ieva et al, 2021) to dismantling systems (Gonzalez & Cokley, 2021;Mason et al, 2021). Only one (Cartwright et al, 2021) (Ratts et al, 2016) with little evidence that the model support's positive student outcomes, specifically for students with marginalized identities (Placeres et al, 2022). Instead, multicultural competence frameworks "allow students, most of whom are White, to feel comfortable talking about culture and diversity without discussing uncomfortable topics" (Williams et al, 2021, p. 260), outcomes that are misaligned with the desired intent of antiracism, abolition, and Black futurity (Davis et al, 2022;Tuck & Yang, 2018).…”
Section: Lack Of Consensusmentioning
confidence: 99%
See 1 more Smart Citation